PENGARUH PELATIHAN PERAWAT TERHADAP PRODUKTIVITAS KERJA PERAWAT DI RUMAH SAKIT PARU DUNGUS KABUPATEN MADIUN - Prayitno, Suhadi (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2019)
ABSTRACT Â A preliminary survey of performance issues, there is still a performance assessment by a nurse who belongs is quite good and less good, surely it will effect conferring on high low productivity generated by nurses, this course is directly proportional to the statement of the head of the HRD (human resource development) stating the attitude and discipline that is still low that will affect productivity. This research aims to know the influence of Training Nurse Against Nurse work productivity in hospital Pulmonary Dungus Madiun Year 2016. This type of research aims is crossectional approach with quantitative. The sample of this research is 47 Nurses in hospital Pulmonary pelaksanan Dungus Madiun, using the method of total sampling. With the use of the correlation Test Product Moment. The results of this research are training nurses categorized either as many as 26 people (55.3%), while nurses were categorized as many as 21 people less well (44.7%). And nurses with high work productivity as much as 24 people (51.1%), while nurses with low work productivity by as much as 23 people (48.9%). Based on the correlation of test Product Moment is obtained a value of 0.02, meaning the value of the sig sig smaller than 0.05 (0.02 < 0.05) showed that there is a sidnifikan between the influence of nurse training with work productivity of nurses in a hospital Lung Dungus keeratan weak denggan Madiun of 0.333. Suggestions that researchers recommend is hospital management should improve training programs, because with the increasing level of training to increase work productivity of nurses that will take a very positive influence with increasing the quality of nursing care. Â Keywords: Coaching, Productivity, Nurse